Assessing emerging beef farmers participation in high-value market and its impact on cattle sales in South Africa - Oduniyi, OS; Antwi, MA; Mukwevho, AN (International Journal of Agricultural Research, Innovation and Technology, 2022)
The participation of emerging farmers in high-value agricultural markets in South Africa cannot be over-emphasized. It is one of the objectives of the government to assist emerging farmers with the necessary resources and programmes to enable them to meet the requirements and participate in high-value markets. The study investigated the impact of participation in the high-value market on cattle production (cattle sold). A systematic random probabilistic sampling technique was used to obtain a sample of 55 emerging beef farmers. Interviews were undertaken using questionnaires to collect data. Descriptive statistics and econometric methods such as Tobit model and a treatment effect model using propensity score matching estimator were employed for the data analysis. The results of binary logit regression from the PSM revealed that participation in a high-value market was significantly affected by age, household size, years of farming and difficulty accessing a high-value market. The average treatment effect of the treated showed a negative impact and decreases the number of cattle sold by 58%. The recommendations informed by the findings from the study are that youth in the study area should be involved in beef farming, appropriate training should be given to the farmers and farmer's advisor should motivate farmers to sell more cattle and participate in a high-value market, and educate them about the requirements to participate in the high value markets. The DARD lease assistance should continue and include the lease of more land. Int. J. Agril. Res. Innov. Tech. 11(2): 27-36, Dec 2021